Penafsiran Ayat Tentang Bersatu dan Larangan Terpecah Belah - Muhlis Aditya; Angelia Revi Marohima; Aisya Karima (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
This article reviews the message of the Al-Qur'an regarding the importance of unity and commitment to the path of truth, as reflected in Surah Ali 'Imran verse 103 and Surah Al-An'am verse 153. Surah Ali 'Imran verse 103 commands Muslims to hold firmly to the ropes of Allah's religion, namely Islam, and prohibits division which can give strength to the people. This verse also reminds of the blessings of brotherhood that Allah bestowed on the early Muslims, especially between the Aus and Khazraj, as a clear example of how guidance can unite hearts that were previously friendly. On the other hand, Surah Al-An'am verse 153 emphasizes that Allah's path is one and straight, while other paths lead to division and deviation. Through a thematic approach and analysis of classical interpretation, this article shows that the unity of the Muslim Ummah can only be achieved if all elements of the Ummah consistently return to the Al-Qur'an and Sunnah, and stay away from circular teachings. Thus, this second verse becomes a strong theological foundation in maintaining the Islamic brotherhood, avoiding including the Ummah from ideological and social divisions that can damage the unity of the Ummah.